Praktek Pembuatan Konsep P5 Dalam Kurikulum PAI - Reo Tommi Pratama; Nur Hasanah; Syawaludin Syawaludin; Nizar Nizar; Mustafiyanti Mustafiyanti (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The practice of creating the P5 concept in the Islamic religious education curriculum is a process aimed at developing understanding and application of the principles of Pancasila and Citizenship Education (P5) in the context of Islamic religious education. The P5 concept refers to five core values, namely Belief in One God, Humanity, Unity, Democracy, and Justice. In the context of the Islamic religious education curriculum, the practice of creating the P5 concept involves the development of learning materials that integrate P5 values into every aspect of Islamic religious education. This is intended to shape students' characters to be virtuous, patriotic, respectful of diversity, and have a sense of law and justice. The process of creating the P5 concept in the Islamic religious education curriculum involves various stages, starting from identifying relevant P5 values to Islamic teachings, developing learning materials that support the integration of these values, to assessing and evaluating the effectiveness of implementing the P5 concept in teaching. With the practice of creating the P5 concept in the Islamic religious education curriculum, it is hoped that students can become a generation with moral awareness, ethics, and adherence to Islamic teachings and Pancasila values as the foundation of the Indonesian state. This also serves as an effort to strengthen national identity and promote unity and harmony among the nation through Islamic religious education based on universal values of humanity and justice.